Sense of Competence, Autonomy and Relatedness during Primary-Secondary Transition: Children Express Their Own Experiences - Hargreaves, Eleanore; Saville, Katya; Buchanan, Denise; Leaton Gray, Sandra; Perryman, Jane; Quick, Laura (International Journal of Educational and Life Transitions, 2022)
This paper contributes a greater understanding of the importance of a sense of competence, autonomy and relatedness to children experiencing the primary-secondary schooling transition, drawing on the perspectives of the young people themselves. We address how the perspectives of transitioning children can further substantiate and illuminate Ryan and Deci’s Self Determination Theory (SDT; Ryan and Deci, 2019). SDT claims that satisfaction of a person’s needs for competence (attainment and confidence), autonomy (self-direction and capacity to critique) and relatedness (feeling affectively bonded to others) allows them to achieve ‘positive-experience and wellness outcomes’ (p.219). We draw on data from two research projects, one a survey study of 288 transitioning children; and one a life-history study of 23 transitioning children. Our findings illustrated the potential benefits of policymakers giving priority to a wider range of conceptions of competence beyond attainment in mathematics/English, in order to support transitioning children’s sense of competence including their self-confidence. Findings also highlighted the need to nurture children’s capacity to recognise and direct their own schooling trajectories more autonomously, directing their energies into engagement with learning and relationships rather than into riling against controls or seeking to avoid humiliation and punishment. Most positively, our data manifested children’s high levels of relatedness to both peers and teachers as they transitioned to new secondary schools. And above all, our data emphasised and exemplified the need for relatedness to accompany children’s strong sense of competence and autonomy during transition.